Analytical Method for Differential Amplifier Offset Voltage Analysis - Baskys, A.; Nickelson, L.; Navickas, R. (Elektronika ir Elektrotechnika, 2011)
The analytical method for differential amplifier offset voltage analysis is presented in the work. The method is developed for the amplifier based on the bipolar junction transistors that operate at high-current density. The transistor model based on the equation of the junction, which takes into account the dependence of majority carrier boundary concentrations on junction voltage that should be considered at high-current density, is used as the base for derivation of input offset voltage equations. The derived equations are valid in the narrow region of current, at which the differential amplifier input offset voltage measurement is provided. The obtained equations allow us to estimate the input offset voltage reduction ways. The results gained using suggested analytical analysis method are confirmed by the numerical investigation of the differential amplifier. Ill. 3, bibl. 11 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.108.2.144